Inferences on pod wall and seed defenses against the brown cowpea coreid bug, Clavigralla tometosicollis Stal ( Hempptera Coreidae) in wild and cultivated Vigna species - Jackai, L.E.N.; Nokoe, S.; Tayo, B.O.; Koona, P. (Wiley, 2001)
Studies were conducted in the laboratory to investigate the different components of the resistance of Vigna vexillata A. Richards, TVnu 72, and several cultivars of cultivated Vigna spp. to infestation and damage by the brown cowpea coreid, Clavigralla tomentosicollis Stäl. The main objective was to determine the different roles of the pod wall and seeds, and the relationship between seed size, number, and damage by this insect. Results showed that both the pod wall and seed clearly contribute different components to the resistance of TVnu 72 to C. tomentosicollis. Analysis of the results suggests that the seed defences and the pod wall pericarp may be more important than are trichomes in this resistance. Seed number was found to influence the extent of damage in a more predictable manner than seed size. However, because both of these traits are generally inversely related and mutually exclusive, their individual effects cannot be completely separated. The implications of these traits in a breeding programme targeted at a specific consumer group are discussed.